Degradasi hidrotermal Kappaphycus alvarezii: Karakter hidrolisat dan kapabilitas sebagai prebiotik: Hydrothermal degradation of Kappaphycus alvarezii: Hydrolysate characteristics and capabilities as prebiotics - Mutmainnah Mutmainnah; Desniar Desniar; Joko Santoso (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2023)
Seaweed Kappaphycus alvarezii as the largest source of polysaccharides from the sea can be a source of prebiotics but is still underutilized. Therefore, this study aimed to determine the effect of heat treatment on the hydrolysate of K. alvarezii and the effectiveness of the addition of the hydrolysate on the characteristics of synbiotic products based on milk fermentation with Lactobacillus plantarum IFO 3074. This study consisted of two stages, namely hydrolysis using a temperature factor (80, 90 and 100°C) and time (1, 2, and 3 hours) and the production of synbiotics based on milk fermentation with the addition of 0.2% seaweed hydrolysate. The results of the first stage of the study showed that the best treatment was 100°C for 3 hours with the highest amount of reducing sugar as an indicator of hydrolysis, which was 0.31 g/100 mL. Then the fermentation stage with addition of hydrolysate obtained microbiological characteristics (number of colonies) and chemical (total titrated acid, pH, and reducing sugar) which are generally significantly different and the value is 9.40 log cfu/mL; 0.28%; 4.48 and 66.78 g/100 mL. The increase in the characteristics of the fermented product with the addition of hydrolysate proves that the hydrolysis process can degrade seaweed polysaccharides into simple molecules (prebiotics) that can be utilized in the growth of probiotics, so that the addition of K. alvarezii hydrolysate has the potential to be developed as a synbiotic-based functional food with low production costs.